The impact of 24-hour sleep deprivation on cognition and inflammatory response in anesthesiologists and nurses in operating rooms - Tao Ma; Long Feng; Guan-Hua Li; Xiu-Yan Sun; Yang Chu; Wen-Hui Zhao; Shuai Feng; Hao Zhang; Wei Wang (Saudi Journal of Anaesthesia, 2025)
Introduction: The effects of acute sleep deprivation on cognitive function and inflammatory responses remain inadequately defined. This study aimed to evaluate changes in cognitive function and inflammatory responses among anesthesiologists and nurses in the operating room following 24-hour shift work-induced sleep deprivation. Material and Methods: Forty anesthesiologists and nurses were assigned to either the sleep deprivation group (n = 20, working from 8:00 AM to 8:00 AM the following day) or the rest control group (n = 20, working regular hours from 8:00 AM to 5:00 PM). All participants underwent assessments of cognitive functions and peripheral blood sample collections for brain-derived neurotrophic factor (BDNF), tumor necrosis factor-alpha (TNF-α), and interleukin-1 beta (IL-1β) at 8:00 AM, 4:00 PM, 0:00, and 8:00 AM the following day. Cognitive functions were assessed using the Trail Making Test and the Stroop Color-Word Test. Results: Cognitive assessments revealed no significant effect on reaction time following one night of sleep deprivation (P > 0.05 for all). However, the learning effect from repeated administrations of the Trail Making Test and the Stroop Color-Word Test did not result in decreased reaction times in the sleep deprivation group (P > 0.05 for all). Increased fluctuations in serum levels of TNF-α and BDNF were observed after 24-hour shift work at 8:00 AM (P < 0.05 for all). Conclusion: Sleep deprivation induced by 24-hour shifts did not impair cognitive performance but did affect learning ability in anesthesiologists and nurses. Additionally, sleep deprivation caused increased fluctuations in serum levels of TNF-α and BDNF at 8:00 AM.